EFFECT OF FEEDING FREQUENCY ON SOME PERFORMANCE INDICES OF THE AFRICAN CATFISH (CLARIAS GARIEPINUS, BURCHEL 1822) JUVENILES (FUDMA JOURNAL OF SCIENCES, 2022)
A nine-weeks feeding trial was carried out to investigate the effect of feeding frequency on the growth performance of the African catfish, Clarias gariepinus. C. gariepinus juveniles (12.72Â±0.45 g) were stocked into 9 tanks at a density of 10 ï¬sh per tank and three different feeding frequencies were tested on triplicate groups for 63 days. Feeding frequency I: fish were fed to apparent satiation only once a day, in the mornings, throughout the experimental period. Feeding frequency II: fish were fed to apparent satiation twice a day, every other day, throughout the experimental period. Feeding frequency III: fish were fed to apparent satiation, twice a day, throughout the experimental period. A commercial catfish diet consisting of 42 % crude protein and 20 Mj Kg-1 gross energy was used. No significant (P>0.05) differences were observed in growth performance or food conversion ratio (FCR) amongst the three different treatments. Similarly, feed intake was not significantly higher in any group as increased feeding was observed when fish in Groups 1 and 2 were fed. This study reveals that feeding strategies such as used in Groups 1 and 2 in this study may neither improve growth performance nor be a good feeding strategy for the reduction of production cost in C. gariepinus farming
Keywords: Clarias gariepinus, feeding frequency, food conversion ratio, growth performance, hyperphagy, restricted feeding